THE FACTORS WHICH INFLUENCE THE RELATIONSHIP BETWEEN A NETWORK’S SYNERGIZING CAPABILITY AND THE INCREASE IN A SALESPERSON’S PERFORMANCE - Ida Bagus Nyoman Udayana; Naili Farida (Journal of Indonesian Economy and Business (JIEB), 2019)
Introduction: This research aims to explore the concept of customer networks in the context of sales. A research model is proposed to explain how a salesperson’s performance is increased by synergizing the network. Background Problems: There are inconsistent research findings on the relationship between adaptive selling and salespeople’s performance. The proposed research question is whether adaptive selling has an effect on a salesperson’s performance through his/her customer networking capability or not? Novelty: the novelty of this research is the analysis of the capabilities of customer networking, based on information sharing, promotion sharing, and knowledge sharing. Research Methods: This research involved 266 salespeople from the soft drinks’ industry. The hypotheses were tested using structural equation modeling. Findings: The results of the study show that adaptive selling is able to increase a salesperson’s performance through their customer networking capability. The customer’s order quality, adaptive selling and communication quality have significant positive effects on the capability of the customer network. Furthermore, the customer’s order quality, retention, and communication quality have significant positive impacts on the salesperson’s performance. The variable which has the most influence on the increase in the salesperson’s performance is communication quality. Conclusion: This study concludes that the ability of the customer networking capability to link between adaptive selling and the salesperson’s performance is real. Additionally, the quality of the customer’s orders, retention and the quality of their communications give significant positive effects to a salesperson’s performance. Therefore, companies should pay special attention to the salespeople who perform best, particularly those who can broaden new networking customers.